The Imperative of Prophetic Responsibility in a Milieu of Moral Bankruptcy and Leadership Failure: Prophet Amos in the Context of Modern-Day Nigeria - Festus Osom Omosor (Universitas Negeri Makassar, 2026)
This study critiques the deplorable moral and leadership condition of the Nigerian nation while examining the role of prophets in nation-building. Against the backdrop of the responsible and reformist engagement of Prophet Amos in eighth-century Israel, the study identifies the failure of prophets, understood here as Christian clerics, to adequately respond to and address the pervasive moral bankruptcy and socio-political problems in modern-day Nigeria. The objective is to confront those who claim to be the mouthpieces of God in Nigeria with their prophetic failures and to call them to conscientiously discharge their divine responsibility of moulding and guiding the Nigerian nation towards the realisation of an ideal society characterised by ethical and moral probity in leadership, which is a necessary condition for a stable, crisis-free society. The study is essentially qualitative and sociological. It employs discourse analysis to examine the prophetic character of Amos, complemented by participant observation, real-life experience, and hands-on knowledge of the Nigerian situation. The study situates Amos' voice of social justice and reformation, emphasising its applicability in a society characterised by moral decay, leadership failure, corruption, and social injustice. Findings reveal that the moral failures of Nigerian society, as manifested in greed, corruption, political manipulation, abuse of power, social injustice, and religious compromise, mirror the circumstances that prompted Amos' call to prophetic judgment. Modelling Amos, the study underscores the imperativeness of prophetic responsibility in addressing the Nigerian problem. It therefore charges prophets, as reformers and nation builders, to speak truth to power without compromise, fear, or favour.